Characterizations of rotundity and smoothness by approximate orthogonalities - Stypuła, Tomasz; Wójcik, Paweł (Annales Mathematicae Silesianae, 2016)
In this paper we consider the approximate orthogonalities in real normed spaces. Using the notion of approximate orthogonalities in real normed spaces, we provide some new characterizations of rotundity and smoothness of dual spaces.